2018
DOI: 10.3390/brainsci8070122
|View full text |Cite
|
Sign up to set email alerts
|

Education and Income Predict Future Emotional Well-Being of Whites but Not Blacks: A Ten-Year Cohort

Abstract: Background: The Minorities’ Diminished Return (MDR) theory is defined as systematically smaller effects of socioeconomic status (SES) on the health and well-being of minority groups when compared to Whites. To extend the existing literature on the MDR theory as applied to the change of mental well-being over time, we investigated Black-White differences in the effects of baseline education and income on subsequent changes in positive and negative affect over a ten-year period. Methods: The Midlife in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 84 publications
9
105
0
Order By: Relevance
“…A number of studies have shown that education generates less income in Blacks than Whites (48,49). In another study, controlling for income explained MDRs of education on SRH.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A number of studies have shown that education generates less income in Blacks than Whites (48,49). In another study, controlling for income explained MDRs of education on SRH.…”
Section: Discussionmentioning
confidence: 90%
“…Under labor market discrimination, highly educated Blacks may have a lower chance to secure high quality, low stress, and high paying jobs (45)(46)(47). Thus highly educated non-Hispanic Blacks make lower income and are more likely to live under poverty despite high educational level, compared to non-Hispanic Whites with the same education (44,48,49). On top of labor market discrimination, interpersonal discrimination is a major risk in the life of highly educated Blacks, because highly educated Blacks are likely to have higher not lower exposure and vulnerability to discrimination (27,(50)(51)(52).…”
Section: Due To Multiple Societal Mechanisms Ses Indicators May Genementioning
confidence: 99%
“…We also observed a mean of 12.8 years of education, which suggests that our sample was a well-educated group. Participants were still living in low SES areas, suggesting that education has smaller than expected effects on changing AA life conditions [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 97%
“…As a result of MDRs , the health effects of SES indicators such as educational attainment and income are diminished for racial and ethnic minority groups. Thus, diverse race/ethnic groups not only vary in their SES (Navarro, 1991(Navarro, , 1990(Navarro, , 1989) but also how their SES turns to health outcomes Assari, Preiser, & Kelly, 2018). As a result, it is "race/ethnicity and SES" not "race/ethnicity or SES" that generates racial and ethnic health disparities (Navarro, 1991(Navarro, , 1990(Navarro, , 1989 Although high education and income reduces exposure to risk factors overall (Lunau, Siegrist, Dragano, & Wahrendorf, 2015;Hackman, Gallop, Evans, & Farah, 2015), Blacks and Hispanics with high education and income report high level of environmental risk factors such as stress , discrimination , and active and passive exposure to tobacco smoke (Assari & Mistry, 2018;Assari & Bazargan, 2009;Assari, Mistry, & Bazargan, 2020).…”
Section: Introductionmentioning
confidence: 99%